Termination of the International Sales Contract from the Point of View of International Courts and Arbitral Tribunals - Mustafa, Mohamed (Journal of Legal Sciences, 2023)
The termination of the international sales contract is one of the solutions that the parties and the law resort to resolve some fundamental violations that occur in the contract for any reason, but determining the fundamental reason that leads to the termination of the contract is the most extreme type of treatment of the fundamental violation that has been interpreted differently by international experts, whether courts international bodies or international arbitration committees. And in relation to the difficulty of determining the fundamental violation that leads to the termination of the contract and the exceptions contained in cases that are considered a fundamental violation and that are not considered a fundamental violation, the research follows the cases that are considered a fundamental violation and that are not considered a violation of the contract from the point of view of international courts and arbitral tribunals. The research concluded that there is no fundamental violation of the contract except that it has an exception from another point of view that is not considered a fundamental violation, and this does not lead to the instability of the rulings reached by international courts and arbitral tribunals.